Comparison Of Extraction Methods For Detecting Hepatitis A Virus In Shellfish (Mystilus Galloprovincialis) Using Tissue Culture Titration, RT-Nested PCR And Real Time RT-PCR - Yong, Han Tek (2009)
Thirty commercial shellfish samples (22 cockles and 8 surf cockles) were collected from several locations around Serdang and tested for the presence of hepatitis A virus (HAV) using a modification of the glycine, polyethylene glycol, Tri-reagent, poly dT bead (GPTT) extraction protocol. None of the 30 tested samples yielded positive results for HAV contamination. Subsequently, detection of HAV in artificially spiked shellfish sample was performed using the modified GPTT method to ensure the negative results were not due to methodological limitations. A parallel comparison between the modified GPTT method and an alternative method, proteinase K-miniMAG in terms of virus recovery and RNA purification efficiency was performed simultaneously. For the first stage of comparison of virus recovery rate, shellfish extract digested by proteinase K resulted in higher recovery when 1 x 104 TCID50/ml of HAV was recovered in contrast to only 4 x 102 TCID50/ ml by the glycine-PEG method. The second stage of comparison was conducted to determine the efficiency of three combinations of virus recovery and RNA purification methods: glycine-PEG-Tri-reagent (M1), glycine-PEG-miniMAG (M2) and proteinase K-miniMAG (M3). Undiluted and serially diluted RNA samples extracted by each method were subjected to RT-nested-PCR. Samples from M1 and M2 were only positive when the samples were undiluted with M2 producing a higher intensity band compared to M1. Samples from M3 were detectable even when diluted up to 100 times indicating that proteinase K digestion was more effective in recovering HAV from shellfish matrix than glycine-PEG and miniMAG was more effective in purifying viral RNA than conventional Tri-reagent. To further investigate the precise efficiency differences among the three methods, a comparison of the Ct values generated by real time RT-PCR was conducted. M3 was again proven to be the most efficient by showing on average the lowest Ct values among the three methods. Lastly, 34 shellfish samples collected in Naples, Italy which were processed using the proteinase K-miniMAG method and analyzed using real time PCR were all found to be negative for HAV. Collectively, these results indicate that a combination of proteinase K with miniMAG that is capable of recovering higher numbers of virus and of yielding higher quantities of intact RNA than the glycine-PEG-Tri-reagent method which was used previously to type the 30 Malaysian samples. Hence this method combination should serve as the method of choice for future detection of HAV from shellfish samples in Malaysia.